Novel Sources of Tolerance to Aluminium Toxicity in Wild Cicer (Cicer reticulatum and Cicer echinospermum) Collections - Vance, Wendy; Pradeep, Karthika; Strachan, Scott R.; Diffey, Simon; Bell, Richard W. (Frontiers in Plant Science, 2021)
In acid soils, the toxic form of aluminium, Al3+, significantly inhibits root growth and elongation leading to less water and nutrient uptake. Previous research had shown differential Al toxicity tolerance among cultivated Cicer arietinum L. (chickpea), however, the potential for developing tolerant cultivars is limited by the narrow genetic diversity of cultivated chickpea. Recent collections from Turkey of wild Cicer species, C. reticulatum and C. echinospermum, have increased the available gene pool significantly, but there has been no large-scale screening of wild Cicer for acid tolerance or Al3+ toxicity tolerance. This study evaluated 167 wild Cicer and 17 Australian chickpea cultivars in a series of screenings under controlled growth conditions. The pH of 4.2 and Al concentrations of 15 and 60 µM Al were selected for large-scale screening based on dose response experiments in a low ionic strength nutrient solution. The change in root length showed better discrimination between tolerant and sensitive lines when compared to shoot and root dry weights and was used as a selection criterion. In a large-scale screening, 13 wild Cicer reticulatum accessions had higher root tolerance index ( 50 %) and eight had higher relative change in root length ( 40 %) compared to PBA Monarch, which showed greater tolerance among the Australian domestic cultivars screened. In general, C. reticulatum species were found to be more tolerant than C. echinospermum; while genetic population groups Ret_5, Ret_6 and Ret_7 from Diyarbakir and Mardin Province were more tolerant than other groups. Among C. echinospermum, Ech_6 from the Siv-Diyar collection site of Urfa province showed better tolerance than other groups. In this first detailed screening of aluminium toxicity tolerance in the new wild Cicer collections, we identified accessions that are more tolerant than current domestic cultivars providing promising germplasm for breeding programs to expand chickpea adaptation to acid soils.